Impact of LCC–HVDC multiterminal on generator rotor angle stability - Oluwafemi Emmanuel Oni; Andrew G. Swanson; Rudiren Pillay Carpanen (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Multiterminal High Voltage Direct Current (HVDC) transmission utilizing Line Commutated Converter (LCC-HVDC) technology is on the increase in interconnecting a remote generating station to any urban centre via long distance DC lines. This Multiterminal-HVDC (MTDC) system offers a reduced right of way benefits, reduction in transmission losses, as well as robust power controllability with enhanced stability margin. However, utilizing the MTDC system in an AC network bring about a new area of associated fault analysis as well as the effect on the entire AC system during a transient fault condition. This paper analyses the fault current contribution of an MTDC system during transient fault to the rotor angle of a synchronous generator. The results show a high rotor angle swing during a transient fault and the effectiveness of fast power system stabilizer connected to the generator automatic voltage regulator in damping the system oscillations. The MTDC link improved the system performance by providing an alternative path of power transfer and quick system recovery during transient fault thus increasing the rate at which the system oscillations were damped out. This shows great improvement compared to when power was being transmitted via AC lines.